Penggunaan Media Sosial Untuk Meningkatkan Brand Merk Produk - Loeky Rono Pradopo; Mulyana Chandra Hadiati; Supriyatno Supriyatno; Evi Dwi Nur Atika; Ayu Kurnisari (Mandalika Institute, 2026)
Social media has become a strategic channel for companies to build and enhance brand merk produk amid increasingly intense market competition. This study aims to analyze the effect of five dimensions of social media usage—intensity of social media use (X1), quality of social media content (X2), user interaction (X3), trust in information (X4), and promotion effectiveness (X5)—on brand merk produk (Y). A quantitative approach with a survey design was employed, involving 103 respondents who are social media users and consumers of the product under study. Data were analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS) using SmartPLS version 4, through measurement model (outer model) evaluation, structural model (inner model) evaluation, and hypothesis testing using bootstrapping (5,000 resamples). The results show that the measurement model meets the criteria for good convergent validity and reliability (loading factor > 0.7; AVE > 0.5; Cronbach’s Alpha and Composite Reliability > 0.7), and adequate discriminant validity based on the Heterotrait-Monotrait Ratio (HTMT) criterion. The R-square value of 0.789 indicates that the five dimensions jointly explain 78.9% of the variance in brand merk produk, categorized as substantial. Hypothesis testing shows that intensity of social media use (β = 0.331; t = 3.925; p = 0.000) and promotion effectiveness (β = 0.381; t = 3.964; p = 0.000) have a positive and significant effect on brand merk produk, while quality of content, user interaction, and trust in information show no statistically significant effect at the 5% level. These findings indicate that a high intensity of social media use and effective promotion are the main drivers of brand merk produk improvement, so companies’ social media strategies should be focused on these two aspects.